Constantine Samuel Rafinesque : A Voice in the American Wilderness - Warren, Leonard, 1924- (Book collections on Project MUSE., 2015)
Constantine Samuel Rafinesque was a quintessential nineteenth-century American scientist and naturalist. Exalted by some, cursed by others, Rafinesque gave Latin names to over 6,700 plant species, was acknowledged by Darwin for his early insights into biological variation, and is frequently mentioned in the great natural history archives. Yet he has been almost forgotten in our own day. During his long career, which included some five years as an innovative professor at Transylvania University in Kentucky, Rafinesque's colorful and sometimes difficult personality led to troubles with his colle.